Efeito do óleo de Caryocar brasiliense Cambess (Pequi) em cepas clínicas de Candida spp. - CORDEIRO , Carolina Borges (2021)
Introduction: pequi is a typical fruit from the Brazilian Cerrado and used in folk medicine against various diseases. Many of its effects are believed to be due to its antioxidant properties. The incidence of fungal infections has increased significantly in recent years and yeasts of the Candida genus are responsible for most of these infections. These yeasts, which live as a commensal in the microbiota of healthy individuals, under certain circumstances can express virulence factors such as enzyme production and biofilm formation, which gives them a pathogenic character and resistance to conventional treatments. Thus, the use of natural compounds such as pequi oil (Caryocar brasiliense Cambess) against pathogenic microorganisms proved to be an alternative treatment. Objective: to determine the effect of pequi oil on virulence mechanisms of clinical strains of Candida albicans, Candida glabrata, Candida parapsilosis, Candida tropicalis and Candida orthopsilosis from different anatomical sites. Methodology: five strains of the Candida genus from the Fungi Collection of the Federal University of Maranhão, NIBA/DEPAT/CCBS were used in this study. The induction of biofilm formation, enzyme and hyphae production was performed in vitro by inoculating the samples in the corresponding media for each test. The strains were identified by the automated Vitek® bioMérieux system and confirmed by molecular biology, using the polymerase chain reaction. The minimum inhibitory concentration (MIC) of oil were performed by microdilution and determined by reading in a spectrophotometer. The percentage of inhibition was calculated taking into account the reading performed at 600 nm. Results: morphological structures and biofilm production capacity were visualized through microscopy. All strains were enzyme producers (amylase, proteinase, lipase and phospholipase), but the highest enzyme activity was found in lipase and the lowest in amylase. The species with the highest enzyme production was C. albicans, with the urine sample being the most prominent for all enzymes. Pequi oil has antifungal property at concentrations from 7.8 μg/ml with a positive result also at 62.5 μg/ml and had its best effect observed at 500 μg/ml, in addition to inhibiting the production of virulence factors (enzyme, biofilm and hyphae) in most samples used for this study, with the exception of Candida albicans (urine) which, in contact with oil, produced a greater amount of enzyme (proteinase) and presented a filamentous form and was identified macroscopically. Conclusion: The potential of the oil and consequently its application as a possible bioproduct for the treatment of infectious diseases of fungal origin of the Candida genus was observed.